Solar radiation variability at Koniczynka near Toruń (Central Poland) in the years 2003–2016 - Kejna, Marek; Uscka-Kowalkowska, Joanna (Bulletin of Geography. Physical Geography Series, 2018)
The paper presents the variability of global solar radiation (K↓) in the agriculture area (Koniczynka near Toruń) in the years 2003–2016. The variability of K↓ has been analysed with reference to atmospheric circulation. The mean yearly sum of K↓ in the analysed period was 3,816.0 MJ m-2. In an annual course the biggest mean values of K↓ occurred in June (608.3 MJ m-2) and the smallest in December (69.0 MJ m-2).The diurnal course of K↓ was symmetrical with respect to the solar noon. Only 44.7% of the solar energy on the top of atmosphere reaches the ground. The highest transmittance occurred in spring and summer, and the lowest in December. The observations revealed an increase in the amount of K↓ (trend 13.6 MJm-2 year-1) and its considerable day-to-day and year-to-year variability. Its increase has been attributed to reduced emissions of aerosols in Poland and Europe (global brightening). The changes of K↓ depend on atmospheric circulation (cyclonic and anticyclonic situations), cloudiness and the optical characteristics of incoming air masses.